Can Hydroxychloroquine Cause G6PD-Related Hemolysis? A Case Study - Khaldun Obeidat; Mohamed A. Yassin (Dubai Medical Journal)
During the pandemic of COVID-19, which started in December 2019, hydroxychloroquine, the drug which was first introduced as antimalarial medication, was widely used to treat this new viral infection, and it was reported in the literature as a safe drug for use in patients with G6PD deficiency; here, we report a 64-year-old male who was started on hydroxychloroquine as treatment for COVID-19 that led to hemolysis, and further investigation showed that the patient is deficient for glucose-6-phosphate dehydrogenase.